The Mitogen-Activated Protein Kinase (MAPK) Pathway: Role in Immune Evasion by Trypanosomatids - Soares-Silva, Mercedes; Diniz, Flavia F.; Gomes, Gabriela N.; Bahia, Diana (Frontiers in Microbiology, 2016)
Leishmania spp and Trypanosoma cruzi are the causative agents of leishmaniasis and Chagas' disease, respectively, two neglected tropical diseases that affect about 25 million people worldwide. These parasites belong to the family Trypanosomatidae and are both obligate intracellular parasites that manipulate host signaling pathways to establish the infection, and also subvert the host innate immune system. Mitogen-activated protein kinases (MAPKs) are serine and threonine protein kinases, highly conserved in eukaryotes, and are involved in signal transduction pathways that are related to modulation of physiological and pathophysiological cell responses. This mini-review highlights the current knowledge about the mechanisms that Leishmania spp and T. cruzi have evolved to target host MAPK signaling pathway, highjack immune response, and in this manner, promote parasite maintenance in the host.